2005
DOI: 10.1002/pros.20189
|View full text |Cite
|
Sign up to set email alerts
|

5α‐dihydrotestosterone inhibits 1α,25‐dihydroxyvitamin D3‐induced expression of CYP24 in human prostate cancer cells

Abstract: We demonstrated, for the first time, that DHT reduces the ability of 1alpha,25-(OH)(2)D(3) to induce 24-hydroxylase expression. Our results not only support the earlier finding of a cross-talk between androgen and vitamin D in human prostate cancer cells but also provide a possible mechanism how androgen and vitamin D signaling pathways may interact.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
16
0

Year Published

2006
2006
2013
2013

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 20 publications
(17 citation statements)
references
References 40 publications
1
16
0
Order By: Relevance
“…CYP24 inhibitor can increase the calcitriol half-life in DU145 cells. Although calcitriol-induced levels of CYP24 mRNA are very dramatic compared with its basal levels, the CYP24 activity is low in LNCaP and PC3 cells, only 0.001% of DU145, and may not be sufficient to cause a significant change in the catabolism of calcitriol (26). Several calcitriol-based combination therapies also showed that CYP24 mRNA abundance is not always associated with the CYP24 activity (42).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…CYP24 inhibitor can increase the calcitriol half-life in DU145 cells. Although calcitriol-induced levels of CYP24 mRNA are very dramatic compared with its basal levels, the CYP24 activity is low in LNCaP and PC3 cells, only 0.001% of DU145, and may not be sufficient to cause a significant change in the catabolism of calcitriol (26). Several calcitriol-based combination therapies also showed that CYP24 mRNA abundance is not always associated with the CYP24 activity (42).…”
Section: Discussionmentioning
confidence: 99%
“…Upon establishing that 10 nmol/L calcitriol combined with 10 Amol/L VES exhibited significant growth inhibition, the following VDR target genes were analyzed under the same experimental conditions. CYP24, containing two VDREs in the promoter, is one of the well-studied calcitriol target genes and is highly inducible by calcitriol in prostate cancer cells (26). It has been shown that induction of CYP24 mRNA can serve as an indicator of calcitriol-mediated genomic activity (27).…”
Section: Translational Relevancementioning
confidence: 99%
“…38 Androgen binding to AR has been reported to slow the degradation of AR leading to prolonged androgen action. 29 A recent study by Lou et al 45 demonstrated that androgens can strongly inhibit calcitriol-induced 24-hydroxylase gene expression and retard the catabolism of calcitriol thus enhancing calcitriol actions in LNCaP cells. Furthermore, the coexistence of functional hormone response elements within the IGFBP-3 promoter 17,23 may act as a hormone response unit with shared accessory elements and accessory factors causing the synergistic transcriptional responses.…”
Section: Discussionmentioning
confidence: 99%
“…The effect of 1␣,25-(OH) 2 D 3 has been studied in prostate cancer cells [11][12][13]. However, 1␣,25-(OH) 2 D 3 exhibits antiproliferative effect only at pharmacological concentrations and may cause hypercalcemia and hypercalciuria, which limit its therapeutic use [14,15].…”
Section: Introductionmentioning
confidence: 99%